Extremely low genetic variability within and among locations of the greenfish holothurian Stichopus chloronotus Brandt, 1835 in Okinawa, Japan - Soliman, Taha; Takama, Okuto; Fernandez-Silva, Iria; Reimer, James D. (PeerJ, 2016)
The greenfish sea cucumber Stichopus chloronotus is an economically and ecologically important sea cucumber species throughout its range. This species is widely distributed, inhabiting coral reefs of the Indo-Pacific Ocean. Our study evaluated population genetic structure and levels of genetic diversity in southern Japan. A total of 180 individuals were collected from eight locations from Okinawa and Okinoerabu Islands and sequenced using mitochondrial 16S ribosomal DNA (16S) and nuclear histone H3 (H3) gene. Only three 16S haplotypes were detected (518 bp) with haplotype diversity ranging from 0 to 0.56 and nucleotide diversity from 0 to 0.1%. H3 showed no variation among the studied locations. It is plausible that such results could be due to a shift to asexual reproduction. Additionally, the presence of the species on the east coast of Okinawa could only be detected in one location and all individuals consisted of a single haplotype. Genetic differences between the east and west coasts of Okinawa have been noticed in other coral reef organisms, and attributed to either ecological or biogeographical historical differences between the coasts due to differing levels of isolation during Pleistocene ice ages. Results from the present study should inform management and conservation policies of S. chloronotus in southern Japan.
Keywords: Sea cucumber; Stichopus chloronotus; Okinawa Island; mtDNA; 16S ribosomal DNA